Medial Patellofemoral Ligament Augmented With a Reinforced Bioinductive Implant Is Biomechanically Similar to the Native Medial Patellofemoral Ligament at Time Zero in a Cadaveric Model - Sean Mc Millan, D.O; Seth Sherman, M.D; Zachary R. Brown, M.S; Erik Brewer, Ph.D; Elizabeth Ford, D.O (Elsevier, 2024)
Purpose: To biomechanically compare primary medial patellofemoral ligament (MPFL) repair (MPFLr) augmented with a reinforced bioinductive implant (RBI) to the native MPFL ligament and a semitendinosus (semi-T) MPFL reconstruction (MPFLR) at time zero. Methods: Four fresh-frozen matched pair cadavers (8 knees) were used to biomechanically compare the native MPFL to augmented MPFLr (n = 4) and semi-T MPFLR (n = 4). The native MPFL (n = 8) was isolated, preserving the femoral and patellar attachments, and pulled to failure. The semi-T was harvested from 1 of the matched pairs and whipstitched, as was a 250-mm × 5-mm RBI. A standard double-bundle docking technique was utilized. The patella was potted and mechanically pulled parallel to the transverse axis until failure in both cohorts. Cyclic creep, load and displacement at failure, failure mode, and stiffness were recorded. Results: Failure load was highest in the RBI with repair group (287 ± 130 N) compared to the native MPFL (219 ± 64 N) and the semi-T group (84 ± 29 N). No statistically significant difference in failure load between the RBI augmentation with repair group and the native ligament (P = .19) were found. The semi-T reconstruction group failed at the least amount of displacement (7.93 ± 3.4 mm) compared to the native MPFL (20.9 ± 9 mm) (P < .01) and the RBI with repair group (33.2 ± 17.7 mm) (P < .02). At 10 mm of displacement, the RBI group (8.3 ± 1.2 N/mm) demonstrated stiffness in the midrange compared to the native MPFL (14.1 ± 7.1 N/mm). Early anchor/tendon pullout failure on the patella side was noted in the semi-T group compared to the RBI group. One reconstruction was excluded from analysis due to poor bone quality. Conclusions: No statistically significant difference was seen between the augmented MPFL repair and the native MPFL in load-to-failure testing. The augmented MPFL repair was observed to have biomechanical properties similar to the native MPFL. MPFLr with RBI augmentation provided consistent stiffness at clinically relevant displacement. Clinical Relevance: Primary MPFL repair and reconstruction using the semi-T graft, while effective, are nevertheless imperfect procedures. MPFL repair has been shown to have higher instability recurrence rates, while the stiffness profile of MPFLR with semi-T is higher than the native MFPL and may lead to knee stiffness, loss of motion, or cartilage damage. The results of this time-zero biomechanical study indicate that the use of an RBI for augmentation of a primary MPFL repair may be a viable alternative to traditional MPFL repair or reconstruction using a semi-T graft.